2013
DOI: 10.1063/1.4804133
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and elastic properties of yttrium gallium garnet under pressure from ab initio studies

Abstract: In this paper, we present an ab initio study within the framework of density functional theory employing the generalized gradient approximation applied to the study of the structural, elastic, and electronic properties of yttrium gallium garnet, Y 3 Ga 5 O 12 , under hydrostatic pressure. The calculated structural ground state properties are in good agreement with the available experimental data. Pressure dependence of the elastic constants and the mechanical stability are analysed up to 90 GPa, showing that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
9
19
0
Order By: Relevance
“…In this position, and due to the ionic size considerations, the RE 3+ ions are expected to predominantly enter in the structure replacing the Y 3+ ions. Moreover, the vibrational modes and the optical properties of the RE 3+ ions in these nano-garnets are also quite similar to those found in the YGG bulk crystal [19][20][21] . The visible and NIR diffuse reflectance spectrum in the range from 200 to 1800 nm was measured using a spectrophotometer with an integrating sphere (Agilent Cary 5000).…”
Section: Ba Experimentalsupporting
confidence: 64%
See 1 more Smart Citation
“…In this position, and due to the ionic size considerations, the RE 3+ ions are expected to predominantly enter in the structure replacing the Y 3+ ions. Moreover, the vibrational modes and the optical properties of the RE 3+ ions in these nano-garnets are also quite similar to those found in the YGG bulk crystal [19][20][21] . The visible and NIR diffuse reflectance spectrum in the range from 200 to 1800 nm was measured using a spectrophotometer with an integrating sphere (Agilent Cary 5000).…”
Section: Ba Experimentalsupporting
confidence: 64%
“…Moreover, a careful calibration for the biological range (292-335 K) has been also carried out. Since the concentration of optically active ions affects the sensitivity of the optical sensor in bulk matrices 20 , this work will also explore whether this effect also occurs in the YGG nano-garnets. Finally, the behavior of the green emissions with temperature is analyzed as a function of the exciting laser wavelength by choosing a blue laser radiation at 488 nm and a nearinfrared (NIR) laser at 800 nm.…”
Section: A Introductionmentioning
confidence: 99%
“…C 11 is higher than C 44 , indicating that in this material the resistance to a shear deformation is weaker than the resistance to a compression. 12 Therefore, our results for LuGG are in good agreement with the reported experimental data for other gallium garnets and suggest that LuGG will become amorphous at around 87 GPa. 4.…”
Section: Elastic Propertiessupporting
confidence: 90%
“…Besides, since phonons play an important role in the electrical, thermal and optical properties of materials it is essential to study their lattice dynamics to go deeper into the physics of these materials. 12 Now we are interested in studying similar effects in our system, to evaluate the modifications related to the possible effect of the ''chemical pressure'' related to size effects when changing Y with a Lu atom. 5 The knowledge of the evolution of the elastic properties and the lattice dynamics of garnets under pressure could allow understanding possible changes occurring in the solid-state properties of the garnet and how they would affect the environment and, hence, the luminescence properties of RE 3+ at high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this is the similar lattice disorder case for the substitution of divalent and trivalent cations in henritermierite [16] and pyrope and grossular [17]. The electronic properties of garnet series which are influenced by the structural distortion are worth of investigating carefully [14] [18][19][20][21]. Cano et al showed that grossular has a direct band gap of 5.22 eV [14].…”
Section: Introductionmentioning
confidence: 95%